한국 노인의 객관적ㆍ주관적 저작능력 평가에 영향을 미치는 요인 - 정효정; Hyo-jung Jung; 민영광; Yong-guang Min; 김효정; Hyo-jung Kim; 이주영; Joo-young Lee; 이은송; Eun-song Lee; 김백일; Baek-il Kim; et al. (대한구강보건학회지, 2018)
Objectives: The purpose of the study was to investigate factors affecting the assessment of objective and subjective masticatory ability in the elderly, and to evaluate masticatory ability assessment more accurately. Methods: A total of 112 participants were recruited after oral examination in senior citizen welfare facilities. The participants’ masticatory ability was evaluated objectively (Mixing ability index; MAI), and subjectively (Key food intake ability; KFIA). Participants’ general characteristics and oral health-related variables were also recorded. Based on masticatory ability assessment, participants were classified as either high or low. IBM SPSS Statistics Ver.23.0 was used for all analyses, including descriptive statistics, Chi-square test, Mann-Whitney U test, Spearman rank correlation, and Logistic regression analysis. Results: Higher masticatory ability was positively correlated with higher scores on MAI and KFIA. Additionally, there was a significant positive correlation between MAI and KFIA. When analyzing factors affecting objective and subjective masticatory ability assessments, Functional tooth units (FTUs) were revealed as a related factor. In subjective masticatory ability assessment, oral moisture, difficulty in chewing, and the Geriatric Oral Health Assessment Index (GOHAI) were also influential factors. Conclusions: In order to accurately assess masticatory ability, it is necessary to use both objective and subjective measures. Additionally, to improve the masticatory ability in the elderly, treatment should be provided to improve overall oral health and satisfaction.